Awareness, use, and need of smart care for older adults: A comparative study based on a survey in Macao, China - Lou, Shiyan; Liu, Hong (Frontiers in Public Health, 2023)
Need is an important factor that determines whether the model of smart care for older adults can be efficiently promoted and ultimately help in effective senior care. Based on a survey among older adults and their caregivers in Macao, this paper studied the awareness, use, and need for smart care goods and services for older adults. Differences appeared among the groups based on the different categories and items of goods and services. The respondents’ awareness, use, and need for smart senior care were generally low, and levels were lower among older adults than among caregivers; older adults were more concerned about spiritual needs, while the caregivers were more concerned about the health and safety of older adults. Correlation studies showed that awareness of smart senior care was positively related to its use, and these two variables were positively correlated to the need for smart senior care. This paper fills in the research gap on the need for smart senior care and can help to promote matching supply and demand to enhance the development of the industry.